Empowering Women Researchers in the New Century: IADR's Strategic Direction. (December 2019) - Ioannidou, E.; Letra, A.; Shaddox, L.M.; Teles, F.; Ajiboye, S.; Ryan, M.; Fox, C.H.; Tiwari, T.; D'Souza, R.N.
Gender inequality in science, medicine, and dentistry remains a central concern for the biomedical research workforce today. Although progress in areas of inclusivity and gender diversity was reported, growth has been slow. Women still face multiple challenges in reaching higher ranks and leadership positions while maintaining holistic success in these fields. Within dental research and academia, we might observe trends toward a more balanced pipeline. However, women continue to face barriers in seeking leadership roles and achieving economic equity and scholarship recognition. In an effort to evaluate the status of women in dental research and academia, the authors examined the role of the International Association for Dental Research (IADR), a global research organization, which has improved awareness on gender inequality. The goal of this article is to review five crucial issues of gender inequality in oral health research and academics—workforce pipeline, economic inequality, workplace harassment, gender bias in scholarly productivity, and work-life balance—and to discuss proactive steps that the IADR has taken to promote gender equality. Providing networking and training opportunities through effective mentoring and coaching for women researchers, the IADR has developed a robust pipeline of women leaders while promoting gender equality for women in dental academia through a culture shift. As knowledge gaps remained on the levels of conscious and unconscious bias and sexist culture affecting women advancement in academics, as well as the intersectionality of gender with race, gender identity, ability status, sexual orientation, and cultural backgrounds, the IADR has recognized that further research is warranted.